Доказать равенство sin^4 a + cos^4 a - sin^6 a - cos^6 a = (sin^2 * 2a)/4

Доказать равенство sin^4 a + cos^4 a - sin^6 a - cos^6 a = (sin^2 * 2a)/4
Гость
Ответ(ы) на вопрос:
Гость
sin^4 a + cos^4 a - sin^6 a - cos^6 a = (sin^2 * 2a)/4  Сгруппируем (sin^4  a - sin^6  a)  + (cos^4  a - cos^6  a) = (sin^2  2a)/4  применив тождества      1- sin ^2  a = cos^2  a                                           1 - cos^2  a = sin^2  a имеем    sin^4 a (1 – sin^2 a) + cos^4 a (1- cos^2 a) = (sin^2 * 2a)/4             sin^4 a * cos^2 a + cos^4 a * sin^2 a = (sin^2 * 2a)/4                      sin^2 a * cos^2 a (sin^2 a + cos^2 a) = (sin^2 * 2a)/4                (4 *sin^2 a * cos^2 a)/4  = (sin^2 * 2a)/4                          (sin^2 *2 a)/4 = (sin^2 * 2a)/4
Не нашли ответ?
Ответить на вопрос
Похожие вопросы